2010
DOI: 10.4238/vol9-2gmr775
|View full text |Cite
|
Sign up to set email alerts
|

Development of a species-diagnostic marker and its application for population genetics studies of the stingless bee Trigona collina in Thailand

Abstract: ABSTRACT. A molecular maker for authenticating species origin of the stingless bee (Trigona collina) was developed. Initially, amplified fragment length polymorphism analysis was made of 11 stingless bee species using 64 primer combinations. A 316-bp band found only in T. collina was cloned and sequenced. A primer pair (CUTc1-F/R) was designed and tested for species-specificity in 15 stingless bee species (239 nests). The expected 259-bp fragment was consistently amplified in all T. collina individuals (134/13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…In this study, relatively high genetic diversity and strong degrees of geographic differentiation of T. pagdeni in Thailand were identified by polymorphism of the 16S RNA gene. This demonstrates the potential of SSCP analysis for assessing intraand inter-specific genetic variations among Tetragonula species in Thailand (Theeraapisakkhun et al 2010). AMOVA revealed significant genetic differentiation among all pairwise comparisons of T. pagdeni.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In this study, relatively high genetic diversity and strong degrees of geographic differentiation of T. pagdeni in Thailand were identified by polymorphism of the 16S RNA gene. This demonstrates the potential of SSCP analysis for assessing intraand inter-specific genetic variations among Tetragonula species in Thailand (Theeraapisakkhun et al 2010). AMOVA revealed significant genetic differentiation among all pairwise comparisons of T. pagdeni.…”
Section: Resultsmentioning
confidence: 89%
“…Recently, Theeraapisakkhun et al (2010) developed a molecular marker in T. collina based on SSCP analysis of an AFLP-derived marker, CUTc1. Genotypic distribution patterns of CUTc1 were different in stingless bee samples from the North-to-Central region (alleles of 259/259 bp corresponding to the AA genotype found in 76/81 nests) and most individuals of T. collina from Peninsular Thailand (alleles of 253/253 bp corresponding to the BB genotype found in 42/53 nests).…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that extant diversity corresponds to a third of actual native bee species richness in the Neotropics (Freitas et al, 2009), including many cryptic species yet to be discovered (Michener, 2007). In fact, previous morphological and molecular studies have revealed cryptic species (Melo, 2003;Rasmussen & Cameron, 2007;Tavares et al, 2007;Koch, 2010) or distinct evolutionary lineages within stingless bees species (Quezada-Euán et al, 2007;Tavares et al, 2007;May-Itzá et al, 2010;Theeraapisakkun et al, 2010;Bonatti et al, 2014;Duarte et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…H. hyaloptera occurs in Thailand and further North up to China but is not known from Malaysia. T. collina , which is widespread in both Malaysia and Thailand [ 19 ] could potentially serve as a model for both studied sesiid species. T. collina lack functional stings and thus cannot inject venom, however they can still bite and chase away intruders [ 20 ].…”
Section: Introductionmentioning
confidence: 99%